Application of graphene from exfoliation in kitchen mixer allows mechanical reinforcement of PVA/graphene film - Zulhelmi, Ismail; Abu Hannifa, Abdullah; Anis Sakinah, Zainal Abidin; Kamal, Yusoh (Springer Berlin Heidelberg, 2017)
Mechanical properties of polyvinyl alcohol (PVA) can be reinforced from the addition of graphene into its matrix. However, pristine graphene lacks solubility in water and thus makes dispersion a challenging task. Notably, functionalisation of graphene is required to accommodate graphene presence in the water. In this work, we have used a kitchen mixer to produce gum Arabic– graphene (GGA) for the first time as filler for mechanical reinforcement of PVA. For the characterisation of exfoliated graphene, mean lateral size of GGA was measured from the imaging by transmission electron microscopy while the mean thickness of graphene was predicted from the obtained spectra by Raman spectroscopy. During the preparation of PVA/graphene film by solution casting, GGA was varied between 0, 0.05, 0.075, 0.10 and 0.15 wt% in concentration. We found that the presence of GGA in PVA improves the tensile stress and elastic modulus about 72–200 and 19–187% from the original values. The data from Halpin–Tsai meanwhile suggested that the mechanical reinforcement of PVA/graphene film is due